2015
DOI: 10.7841/ksbbj.2015.30.4.166
|View full text |Cite
|
Sign up to set email alerts
|

Production of Liquiritigenin with Cell-based Biotransformation and Its Anti-Aging Activity

Abstract: In this study, an efficient whole cell-based biotransformation for the production of liquiritigenin was developed using Laetiporus sulphureus CS0218 as biocatalyst and aqueous extracts of Glycyrrhiza uralensis as co-substrate, respectively. In order to determine the efficacy of this method, the optimal bioconversion conditions including mycelial growth, three important enzyme activities (β-glucosidase, α-rhamnosidase and β-xylosidase), and apparent viscosity of culture broth were monitored. After optimization,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…However, the mean content of liquiritigenin, an ERβ marker compound, in G. uralensis, is very low [21,39]. Hwang et al (2015) reported the bioconversion of liquiritin into liquiritigenin using Laetiporus sulphureus to increase liquiritigenin content in licorice; however, their study focused on liquiritin and liquiritigenin contents, but not on the bioconversion of associated compounds, such as liquiritin apioside and isoliquiritin [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, the mean content of liquiritigenin, an ERβ marker compound, in G. uralensis, is very low [21,39]. Hwang et al (2015) reported the bioconversion of liquiritin into liquiritigenin using Laetiporus sulphureus to increase liquiritigenin content in licorice; however, their study focused on liquiritin and liquiritigenin contents, but not on the bioconversion of associated compounds, such as liquiritin apioside and isoliquiritin [16].…”
Section: Introductionmentioning
confidence: 99%